Identifying barriers to shared decision‐making about bariatric surgery in two large health systems. Issue 2 (12th January 2023) - Arterburn, David; Tuzzio, Leah; Anau, Jane; Lewis, Cara C.; Williams, Neely; Courcoulas, Anita; Stilwell, Diana; Tavakkoli, Ali; Ahmed, Bestoun; Wilcox, Margie; Fischer, Gary S.; Paul, Kathleen; et al.
Abstract: Objective: Prior research suggests shared decision‐making (SDM) could improve patient and health care provider communication about bariatric surgery. The aim of this work was to identify and prioritize barriers to SDM around bariatric surgery to help guide implementation of SDM. Methods: Two large US health care systems formed multidisciplinary teams to facilitate the implementation of SDM around bariatric surgery. The teams used a nominal group process approach involving (1) generation of multilevel barriers, (2) round‐robin recording of barriers, (3) facilitated discussion, and (4) selection and ranking of barriers according to importance and feasibility to address. Results: One health system identified 13 barriers and prioritized 5 as the most important and feasible to address. The second health system identified 14 barriers and prioritized 6. Both health systems commonly prioritized six barriers: lack of insurance coverage; lack of understanding of insurance coverage; lack of organizational prioritization of SDM; lack of knowledge about bariatric surgery; lack of interdepartmental clarity between primary and specialty care; and limited training on SDM conversations and tools. Conclusions: Health systems face numerous barriers to SDM around bariatric surgery, and these can be easily identified and prioritized by multistakeholder teams. Future research should seek to identify effective strategies to address these common barriers.